Application of Analytical Hierarchy Process (AHP) Method in Determining Dike Construction for Handling Tidal Flood - Henny Pratiwi Adi (Universitas Islam Sultan Agung, 2020)
Tambak Lorok in Semarang is one of the areas that often undergoes tidal floods. The construction of dam and dike infrastructure is an effort to overcome tidal floods. As one part of the flood control system, the dike has an important role. The construction projects requires an alternative selection method of dike construction in order to function optimally. This research aims to determine the order of priority criteria and alternative construction of dikes. The data were obtained through questionnaires to experts in the field of dike construction. The aspects of criteria used to analyze alternative dike construction are : functions and benefits, site conditions, costs and construction implementation. The dike construction alternatives include a Concrete Sheet Pile (CSP), Parapet Wall with reinforced Corrugated Concrete Sheet Pile/CCSP and landfill with Geotube Components. The questionnaire were processed using the Analytical Hierarchy Process (AHP) method with the Expert Choice v.11 application. The results showed consistency ratio (CR) of 5%, which means that research data were consistent and could be accounted for. Based on weighting in pairwise comparisons, the priority criteria in selecting type of dike construction are : functions and benefits (33%), site conditions (32%), cost (18%) and construction implementation (17%) The priority alternative dike construction is reinforced Corrugated Concrete Sheet Pile/CCSP (39.7%), landfill with geotube components (3.28%) and Cylindrical Concrete Piles (CSP) (27.5%). Dike construction with reinforced CCSP is a top priority in the handling of tidal floods in the Tambak Lorok.